Understanding resilience - Wu, Gang; Feder, Adriana; Cohen, Hagit; Kim, Joanna J.; Calderon, Solara; Charney, Dennis S.; Mathé, Aleksander A. (Frontiers in Behavioral Neuroscience, 2013)
Resilience is the ability to adapt successfully in the face of stress and adversity. Stressful life events, trauma and chronic adversity can have a substantial impact on brain function and structure, and can result in the development of PTSD, depression and other psychiatric disorders. However, most individuals do not develop such illnesses after experiencing stressful life events, and are thus thought to be resilient. Resilience as successful adaptation relies on effective responses to environmental challenges and ultimate resistance to the deleterious effects of stress, therefore a greater understanding of the factors that promote such effects is of great relevance. This review focuses on recent findings regarding genetic, epigenetic, developmental, psychosocial and neurochemical factors that are considered essential contributors to the development of resilience. Neural circuits and pathways involved in mediating resilience are also discussed. The growing understanding of resilience factors will hopefully lead to the development of new pharmacological and psychological interventions for enhancing resilience and mitigating the untoward consequences.